Regioselective Syntheses of Fluorinated Cyclopentanone Derivatives: Ring Construction Strategy Using Transition-Metal–Difluorocarbene Complexes and Free Difluorocarbene - Fuchibe, Kohei; Takayama, Ryo; Aono, Tatsuya; Hu, Ji; Hidano, Tomohiro; Sasagawa, Hisashi; Fujiwara, Masaki; Miyazaki, Shinji; Nadano, Ryo; Ichikawa, Junji (Synthesis, 2018)
The syntheses of fluorinated cyclopentanone derivatives, which have pharmaceutical and agrochemical importance are reported. The catalytic reaction of copper(I) and nickel(II) difluorocarbenes with silyl dienol ethers afforded 4,4-difluoro- and 5,5-difluorocyclopent-1-en-1-yl silyl ethers, respectively. The fluorine-directed and -activated Nazarov cyclization of 1-fluorovinyl vinyl ketones, which were prepared from silyl dienol ethers and free difluorocarbene, proceeded efficiently to afford 2-fluorocyclopent-2-en-1-ones. Moreover, fluorine-directed Nazarov cyclizations of 2,2-difluorovinyl vinyl ketones and 1-(trifluoromethyl)vinyl vinyl ketones afforded 3-fluorocyclopent-2-en-1-ones and 5-(trifluoromethyl)cyclopent-2-en-1-ones, respectively. In addition, derivatization of ring-difluorinated products also provided 3-fluorocyclopent-2-en-1-ones.
Keywords: fluorine; carbene complexes; carbocation; difluorocarbene; Nazarov cyclization; cyclopentanones; organocatalysts